Earprint recognition using deep learning technique - Arwa H. Salih Hamdany; Aseel Thamar Ebrahem; Ahmed M. Alkababji (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
Earprint has interestingly been considered for recognition systems. It refers to the shape of ear, where each person has a unique shape of earprint. It is a strong biometric pattern and it can effectively be used for authentications. In this paper, an efficient deep learning (DL) model for earprint recognition is designed. This model is named the deep earprint learning (DEL). It is a deep network that carefully designed for segmented and normalized ear patterns. IIT Delhi ear database (IITDED) version 1.0 has been exploited in this study. The best obtaining accuracy of 94% is recorded for the proposed DEL.